Studien zur literaturwissenschaftlichen Imagologie Das literarische Werk F. M. Dostoevskijs aus imagologischer Sicht mit besonderer Beruecksichtigung der Darstellung Polens - Swiderska, Malgorzata (Slavistische Beitraege, 2001)
The dissertation originally aimed to critically examine all of Dostoevsky's works, including journalism, in which Poland, i. Polish figures and historical persons or the Polish history and culture occur. However, because of the excessive scope of this text corpus, the proposed project had to be limited to the interpretation of Dostoevsky's literary works. As a desideratum of research remains the investigation of the relations between the literary and journalistic works Dostoevskijs persist. At the same time, however, the investigation had to be extended to a terminological-methodological examination of "foreignness" or "alterity research", because the previous inconsistent methods and diffuse terminologies did not permit a sufficiently differentiating analysis.